2018
DOI: 10.3126/jaim.v7i1.19577
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Hypertension in a Rural Community of Western Nepal: A Cross Sectional Study

Abstract: Background and aim: Hypertension is a major risk factor for cardiovascular disease. Hypertension evolved as a major public problem in urban populations of many countries including Nepal, but little is known about its prevalence and risk factors in rural areas. The objective of our study was to assess the prevalence of and risk factors associated with hypertension.Methods: A community-based cross-sectional survey was carried out in November 2017 in a four days health camp where peoples from ward number eight of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 14 publications
2
25
2
Order By: Relevance
“…7 Studies conducted in different areas of Nepal show a variation in the prevalence of HTN. It is 41.55% in a rural area, 8 28.9% in semiurban, 9 32.5% in an urban area 10 and 48% in the midwestern region. 11 Likewise, it is 25.1% in people above 18 years of age 12 and in general, there is an increasing trend of HTN.…”
Section: Introductionmentioning
confidence: 97%
“…7 Studies conducted in different areas of Nepal show a variation in the prevalence of HTN. It is 41.55% in a rural area, 8 28.9% in semiurban, 9 32.5% in an urban area 10 and 48% in the midwestern region. 11 Likewise, it is 25.1% in people above 18 years of age 12 and in general, there is an increasing trend of HTN.…”
Section: Introductionmentioning
confidence: 97%
“…Thapliyal et al 18 and Singh N et al 22 observed male predominance for hypertension 58.7% versus 41.3% and 59.9% versus 40.1% respectively. In contrast, Kafle et al 19 Ponnaganti et al 23 and Ntuli et al 20 observed female preponderance of 60% and 56.4% and 63% respectively. Our observations are similar to above studies.…”
Section: Gender Distributionmentioning
confidence: 87%
“…In the present study we observed an overall prevalence of hypertension as 43.3% and this was significantly associated with age, gender, education. Kafle et al 19 and Ntuli et al 20 in their studies observed the prevalence of hypertension to be 41.5% and 41.4% respectively. Singh N et al 22 studied hypertension among adolescents and observed the prevalence of hypertension to be 15.3% (14.0% among boys and 17.3% among girls).…”
Section: Prevalencementioning
confidence: 89%
See 2 more Smart Citations